Emily climbs - Montgomery, L. M. (2014)
Thirteen-year-old Emily Starr, desperate to join her friends at high school in nearby Shrewsbury, agrees to Aunt Elizabeth's requirement that she stay in town with her Aunt Ruth, despite Ruth's refusal to allow Emily to follow her dream of becoming a writer.
Keywords: Orphans